"Health in the English Language": A Partnership With the Alaska Literacy Program - Jinia Sarkar; Arreyellen Salyards; Joan Riley (SLACK Incorporated, 2019)
Background: Health literacy is an issue that is influenced by social determinants and improved by community-based initiatives. Enhancing health literacy can lead to patient engagement, appropriate use of health care, and improved health outcomes. Understanding the community stories by working with vulnerable populations, such as English language learners (ELL), can help inform other health literacy projects on how to enable ELL immigrants to be involved in their health care. Brief Description of Activity: "Health in the English Language" was an 8-week course based on the social view of health literacy that was created and taught by university students. This curriculum was implemented at the Alaska Literacy Program (ALP) during the summer of 2018 in Anchorage, Alaska. Course participants were adult ELL. Implementation: Throughout the summer, the course curriculum was adapted to fit students' needs. Course participants completed open-ended evaluations during the class, and feedback was obtained via interviews with leaders in the community and leaders at ALP. Community organizations were brought into the classroom using resource sheets and an end-of-course community health fair. Results: Student evaluations identified important themes of managing health care and medications, as well as learning new words. Feedback from ALP and community partners highlighted active teaching styles and how the course benefited the community. The results reflect the impact the course had on increasing student confidence, knowledge, and skills to interact with health care providers. The course created a culture that facilitated the ability of immigrant community members to access health resources. The feedback received demonstrated the importance of university students partnering with nonprofits to create effective health literacy programs that are community centered. Lessons learned: Similar programs can be replicated using community and university partnerships to address health literacy problems.